Poor Adherence to Lung Protective Mechanical Ventilation in Pediatric Acute Respiratory Distress Syndrome - Ward, Shan L (Pediatr Crit Care Med, 2016)
OBJECTIVE: To determine the frequency of low tidal volume ventilation (LTVV) in pediatric acute respiratory distress syndrome (PARDS), and assess if any demographic or clinical factors improve LTVV adherence. DESIGN: Descriptive post-hoc analysis of 4 multicenter PARDS studies SETTING: 26 academic pediatric intensive care units PATIENTS: 315 PARDS patients MEASUREMENTS AND MAIN RESULTS: All patients who received conventional mechanical ventilation at hours 0 and 24 of PARDS who had data to calculate ideal body weight (IBW) were included. Two cutoff points for LTVV were assessed: ≤6.5mL/kg IBW and ≤8mL/kg IBW. Of 555 patients, we excluded 240 for other respiratory support modes or missing data. The remaining 315 patients had a median PF ratio of 140 (IQR 90–201), and there were no differences in demographics between those who did and did not receive LTVV. With TV cutoff of ≤6.5mL/kg IBW, the adherence rate was 32% at hour 0 and 33% at hour 24. A LTVV cutoff of TV ≤8mL/kg IBW resulted in an adherence rate of 58% at hour 0 and 60% at hour 24. LTVV use was no different by severity of PARDS nor did adherence improve over time. At hour 0, overweight children were less likely to receive LTVV ≤6.5mL/kg IBW (11% overweight vs 38% non-overweight, p=0.02); no difference was noted by hour 24. Furthermore, in the overweight group, using admission weight instead of IBW resulted in misclassification of up to 14% of patients as receiving LTVV when they actually were not. CONCLUSIONS: LTVV is underused in the first 24 hours of PARDS. Age, PRISM-III, and PARDS severity were not associated with improved LTVV adherence, nor did adherence improve over time. Overweight children were less likely to receive LTVV strategies in the first day of illness.